GAME-BASED EDUTAINMENT LEARNING MEDIA INNOVATION TO INCREASE STUDENT MOTIVATION AND UNDERSTANDING - Astuti, Mirna; Farahah Kamilatun Nuha; Sri Karmila; Mahjati (Auladuna: Jurnal Pendidikan Dasar Islam, 2025)
A challenge in education nowadays is the incompatibility between learning media used and student characteristics, which results in low educational effectiveness in developing competitive and ethical individuals. This study aimed to examine the selection of appropriate learning media based on student characteristics as an effort to improve the quality and effectiveness of learning. The research method used was qualitative with a case study approach, conducted on the fifth-grade students at SDN Minomartani. Data were collected through observation, interviews, and documentation of the learning process and media used by teachers. The results of the study indicated that edutainment-based learning media, especially game media, could increase student motivation, engagement, and understanding of learning materials. This media combined elements of education and entertainment to create a fun and meaningful learning experience. However, there were obstacles to its implementation, requiring adapted media so that it could be accessed through school facilities such as computers.